Eating India : an odyssey into the food and culture of the land of spices - Banerji, Chitrita (New York : Bloomsbury USA, 2007)
"In Eating India, award-winning food writer Chitrita Banerji takes readers on an odyssey through a national cuisine formed by generations of arrivals, assimilations, and conquests. With each wave of newcomers - ancient Aryan tribes, Persians, Middle Eastern Jews, Mongols, Arabs, Europeans - have come new innovations in cooking, and new ways to apply India's rich native spices, poppy seeds, saffron, and mustard to the vegetables, milks, grains, legumes, and fishes that are staples of the Indian kitchen."--BOOK JACKET.
Ch. 1. Bengal : land of a thousand rivers -- Ch. 2. In pursuit of the Portuguese : from Bengal to Goa -- Ch. 3. Road food on the highway -- Ch. 4. A southern thali in Karnataka -- Ch. 5. The anglo-Indian table -- Ch. 6. Pilgrimage and pageantry in Amritsar -- Ch. 7. Banquets of the imperial palace - Muslim style -- Ch. 8. Benaras : feasting and fasting in Shiva's City -- Ch. 9. Art and texture on the Gujarati platter -- Ch. 10. Bombay : city by the sea -- Ch. 11. Kerala : Rich Cuisines of the Pepper Kingdom -- Ch. 12. The vanishing jews of India -- Ch. 13. The indigenous pot -- Ch. 14. Saffron desires.
Keywords: Diet -- India; Food habits -- India; Cooking, Indic; India -- Social life and customs